Urdu Tadreesi Muawnaat Miyad Awal KG - The City School (Lahore The City School)
A resource pack designed for early Urdu language learning in Kindergarten, focusing on foundational language skills.
Includes exercises for early Urdu language learning.
For Kindergarten children
Keywords: Urdu language - Study and teaching (Primary)-Early childhood education